(untitled) (Research, Society and Development, 2020)
This work presents a study on the use of solar energy for charging electric cars with the objective of evaluating the electricity savings for the “Sistema Interligado Nacional” (SIN) and the reduction of greenhouse gases by the implementation of photovoltaic systems in the grid at gas stations recharge in Brazil. For the supply of two vehicles of the Caoa Cherry Arrizo 5e model, daily, with 50kW battery recharge during the period of one hour, the on-grid systems were dimensioned for all gas stations in each state of Brazil, registered in the “Agência Nacional do Petróleo, Gás Natural e Biocombustíveis” (ANP), considering data from the Brazilian capitals. The calculations of the dimensioning of the systems obtained show the benefits achieved with the saving of electric energy from the generation anual of 1.436.683 MWh, and with an annual reduction of greenhouse gas emissions of tonnes of 107.751 CO2. As concluded by analyzing the results, the benefits achieved with the implementation of systems.